Cover Picture: Silicon Meets Cyclotron: Muon Spin Resonance of Organosilicon Radicals / The Pentamethylcyclopentadienylsilicon(II) Cation: Synthesis, Characterization, and Reactivity / Enantioselective Construction of Quaternary Stereogenic Carbon Atoms by the Lewis Base Catalyzed Additions of Silyl Ketene Imines to Aldehydes / Iron Silicates, Iron‐Modulated Zeolite Catalysts, and Molecular Models Thereof / Ultrathin Silica Films: The Atomic Structure of Two‐Dimensional Crystals and Glasses / Preparation of a Sulfo‐Group‐Containing Rod‐Like Polysilsesquioxane with a Hexagonally Stacked Structure and Its Proton Conductivity / [2+2+1] Cycloadditions of Bis(dialkylamino)acetylenes with SiI2(Idip): Syntheses and Reactivity Studies of Unprecedented 2, 3, 4, 5‐Tetraamino‐1 H‐siloles / Dynamic Complexation of Copper(I) Chloride by Carbene‐Stabilized Disilicon (Chem. Eur. J. 30/2014). Issue 30 (21st July 2014) - West, Robert; Samedov, Kerim; Percival, Paul W.; Jutzi, Peter; Denmark, Scott E.; Wilson, Tyler W.; Burk, Matthew T.; Pinkert, Denise; Limberg, Christian; Büchner, Christin; Lichtenstein, Leonid; Yu, Xin; et al.
<x xml:space="preserve">Abstract</x> The cover picture highlights eight of the papers published in this themed issue, specially put together for the 17th International Symposium on Silicon Chemistry. In the top row from left to right: R. West et al. (p. 9184 ff.), P. Jutzi (p. 9192 ff.), and S. E. Denmark et al. (p. 9268 ff.). In the middle row: left C. Limberg and D. Pinkert (p. 9166 ff.) and right H.‐J. Freund et al. (p. 9176 ff.). In the bottom row from left to right: Y. Kaneko et al. (p. 9394 ff.), A. Filippou et al. (p. 9280 ff.), and G. H. Robinson et al. (p. 9208 ff.). The range of papers reflects how silicon chemistry can provide a platform for synergistic solutions through novel method developments of synthetic and analytical tools and the interconnection of different disciplines in molecular and materials chemistry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>